The analysis of relationship between participation-30 index in Turkey and commodity markets, national and international indexes - Mustafa Kevser; Mesut Doğan (Financial Studies, 2020)
The aim of this study is to demonstrate the relationship between Participation-30 index in Turkey and commodity markets, national, international indexes. Islamic finance is increasingly being the research subject of finance literature. Islamic finance shaped by religious principles and prohibits investing areas that the religion doesn't consider appropriate. In 2011, the Participation-30 index consisting of stocks in accordance with the participation banking principles was created in Turkey. The participation index is a stock exchange index in which stock selections are made based on index rules. Then, in 2014, the Participation-50 index and Model Portfolio index were created, and three participation indexes were started to be calculated. Islamic finance mainly operates on the basis of profit and loss sharing and supports the real sector. In this context the activity fields of the companies which are operating in participation indexes are based on production of goods and services so that the indexes have a special importance for commodity markets and commodity indexes. As the results of our research, one-way causality between Participation-30 index and Dow Jones Islamic Market was determined. However, we determined bi-directional causality between Participation-30 index and BIST 100 index.
Keywords: G10; G15; 330; Participation Index; Islamic Finance; Borsa İstanbul; Dow Jones; Commodity